2019
DOI: 10.1088/1361-6560/ab0472
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of myocardial uptake rate constants in dynamic small-animal SPECT using a cardiac phantom

Abstract: Myocardial blood flow and myocardial blood flow reserve (MBFR) measurements are often used clinically to quantify coronary microvascular function. Developing imaging-based methods to measure MBFR for research in mice would be advantageous for evaluating new treatment methods for coronary microvascular disease, yet this is more challenging in mice than in humans. This work investigates microSPECT's quantitative capabilities of cardiac imaging by utilizing a multipart cardiac phantom and applying a known kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…These plots show that the first few iterations yielded a sharp decrease in bias with an initially small increase in standard deviation. This is consistent with previously published results (Johnson et al 2019), where it was concluded that higher iterations (approximately 20 with 4 subsets) and no smoothing provided better quantitative performance.…”
Section: Image Reconstructions and Contrast-recovery Coefficientsupporting
confidence: 93%
See 3 more Smart Citations
“…These plots show that the first few iterations yielded a sharp decrease in bias with an initially small increase in standard deviation. This is consistent with previously published results (Johnson et al 2019), where it was concluded that higher iterations (approximately 20 with 4 subsets) and no smoothing provided better quantitative performance.…”
Section: Image Reconstructions and Contrast-recovery Coefficientsupporting
confidence: 93%
“…First, the same phantom and protocol could be used in microPET to allow for a direct application-specific image-quality comparison between the two modalities. Also, using the alternative form of the phantom from previous work (Johnson et al 2019), dynamic imaging accuracy can be assessed while utilizing different K 1 and k 2 uptake parameters appropriate for different radiotracers, to allow for evaluation of the utility of different radiotracers for cardiac imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientists are trying to develop sequences that can operate in an interleaving fashion with other sequences or motion models which can help predict motion at any given time during the acquisition. An example of parallel sequences is given by Johnson et al, who incorporated six degrees of freedom motion tracking spherical three-dimensional navigators into a turbo-FLASH sequence with no detrimental impact to image quality [40]. These models use minimal MRI information to correlate each motion of different parts of the body with a surrogate signal, which can be obtained from an external device or another MRI sequence-and this is why we refer to them as hybrid tracking methods.…”
Section: Motion Estimationmentioning
confidence: 99%